2008
DOI: 10.1111/j.1600-079x.2007.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of melatonin in regulating matrix metalloproteinase‐9 via tissue inhibitors of metalloproteinase‐1 during protection against endometriosis

Abstract: Endometriosis is a gynecological disease of women and plausibly regulated by matrix metalloproteinases (MMPs). However, mechanisms of alterations in MMPs during endometriosis remain unclear. Human endometriotic tissues possessing varying degrees of severity were examined for expression of MMPs and tissue inhibitors of metalloproteinase (TIMP)-1. In addition, endometriosis was generated in mice and endometriotic tissues were tested for MMP-9 activity. Results show significant upregulation of secreted and synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 59 publications
6
65
0
Order By: Relevance
“…MMPs are involved in the development processes of experimental colitis (Esposito et al 2008b), endometriosis (Paul et al 2008), liver injury (Mishra et al 2011), traumatic experimental spinal cord injury (Esposito et al 2008a), acute ischemic stroke (Ramos-Fernandez et al 2010), and neurodegenerative diseases (Reyes et al 2009, Rosenberg 2009, Bauer et al 2010. Meanwhile, many studies also show that MMPs have contributed to tumor invasion, metastasis, and angiogenesis (Toth & Fridman 2001, Zhang et al 2003, Kessenbrock et al 2010, Pratheeshkumar & Kuttan 2011.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are involved in the development processes of experimental colitis (Esposito et al 2008b), endometriosis (Paul et al 2008), liver injury (Mishra et al 2011), traumatic experimental spinal cord injury (Esposito et al 2008a), acute ischemic stroke (Ramos-Fernandez et al 2010), and neurodegenerative diseases (Reyes et al 2009, Rosenberg 2009, Bauer et al 2010. Meanwhile, many studies also show that MMPs have contributed to tumor invasion, metastasis, and angiogenesis (Toth & Fridman 2001, Zhang et al 2003, Kessenbrock et al 2010, Pratheeshkumar & Kuttan 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse model it was shown that melatonin down-regulated proMMP-9 and MMP-3 expression and activity, and enhanced the expression of a natural inhibitor of MMPs known as TIMP-1 (tissue inhibitors of metalloproteinases) in a dose-dependent manner. The preventive and therapeutic action in endometriosis-like lesions was confirmed, with an increased apoptotic index (34,48). Our study showed that treatment with melatonin effectively regressed endometriotic explants in a rat model.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it may interfere with the oxidative stress seen in endometriosis. It may also have an impact on the extracellular matrix remodelling seen in this disease, through the regulation of the zinc-requiring proteolytic enzymes MMPs, as there is indirect evidence that melatonin inhibits the production of adhesion molecules that promote the binding of leukocytes to endothelial cells (32)(33)(34). Therefore, melatonin may be an effective treatment modality in endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…It caused regression and atrophy of endometriotic lesions in rats. It also, had a more pronounced regression of surgically induced endometriotic foci when compared with letrozole in a rat model 42,43 . Th e possible eff ect of melatonin on the regulation of endometriosis was tested by interfering with matrix metalloproteinase activity in the mice model.…”
Section: Melatoninmentioning
confidence: 88%